The Effectiveness of Prone Positioning in Patients with Acute Respiratory Distress Syndrome: A Literature Review - Giri Susanto; Lestari Sukmarini (Universitas Aisyah Pringsewu, 2022)
Acute respiratory distress syndrome (ARDS) is connected with the high mortality rate. The syndrome appears in the form of a decrease in pulmonary compliance which causes mechanical changes and gas exchange in the lungs resulting in hypoxemia which is indicated by a decrease of oxygen saturation. Prone positioning (PP) can be an intervention in moderate to severe respiratory disorders in ARDS, which aims to increase oxygen saturation. Objective: This study aims to determine the extent to which prone positioning given to ARDS patients can increase oxygen saturation. This study applies the literature review method. The search for the literature used the scientific database, such as Proquest, ScienceDirect, and Pubmed/MEDLINE with the publication years of 2019-2021. Total of 1332 articles were selected, there are 11 articles that fulfill the criteria. The review results of the 11 articles show that prone positioning has been able to increase oxygen saturation in patients with ARDS, with varying durations of pronation. The average duration of pronation is 30 to 90 minutes. The use of prone positioning can increase oxygenation and the ability of the respiratory system in patients with ARDS. The application of prone positioning in patients with moderate to severe respiratory disorders is considered quite safe. Abstrak: Acute respiratory distress syndrome (ARDS) dikaitkan dengan angka kematian yang tinggi. Sindrom yang muncul berupa penurunan komplians paru, yang menyebabkan perubahan mekanik dalam paru-paru dan pertukaran gas yang mengakibatkan hipoksemia yang ditunjukkan dengan penurunan saturasi oksigen. Posisi pronasi (PP) dapat menjadi satu intervensi pada gangguan pernafasan sedang hingga berat pada ARDS, yang bertujuan meningkatkan saturasi oksigen. Studi ini bertujuan untuk mengetahui sejauh mana pemberian posisi pronasi pada pasien ARDS dapat meningkatkan saturasi oksigen. Studi ini menggunakan metoda tinjauan literatur. Pencarian literatur menggunakan database ilmiah antara lain Proquest, ScienceDirect, dan Pubmed/medline dengan tahun publikasi 2019-2021. Dari total 1332 artikel yang diseleksi, ada 11 artikel yang memenuhi kriteria. Hasil tinjauan dari 11 artikel menunjukkan bahwa posisi pronasi mampu meningkatkan saturasi oksigen pada pasien dengan ARDS, dengan durasi pemberian posisi pronasi yang berbeda-beda. Rata -rata durasi pemberian posisi pronasi adalah 30-90 menit. Penggunaan posisi pronasi mampu meningkatkan oksigenasi dan kemampuan sistem pernafasan pada pasien dengan ARDS. Penerapan posisi pronasi pada pasien dengan gangguan pernapasan sedang hingga berat dinilai cukup aman.